PERAN PENDIDIK DAN KEPEMIMPINAN PENDIDIKAN DALAM PENGUATAN PENDIDIKAN KARAKTER - Rindiana, Rani Irmawati; Rahmat, Rahmat; Bestari, Prayoga (Program Studi PPKn, Fakultas Keguruan dan Ilmu Pendidikan Universitas Buana Perjuangan Karawang, 2025)
This study aims to explain the role of civic education in shaping the civic character of students through a value-based approach to civic education in higher education in order to foster good citizenship. Civic education in schools, especially junior high schools, aims to help students become the future intellectuals of the country, good people who understand the core philosophical values of their country, have strong individuality, have broad knowledge, and are able to act in a civilized and democratic manner to become good citizens. The method used in this research is a descriptive literature study using data sources from journals, books, and related scientific studies. The results of this study indicate that Civic Education, as a medium for character education, must not only instill values in students but also be able to internalize values based on Pancasila to serve as the content of one's conscience.